Introception of Moral Values as a Task and Challenge for an Early School Education Teacher - Krystyna Chałas; Ewelina Winiarczyk (Maria Curie-Skłodowska University, Lublin, Poland, 2018)
Upbringing towards values, as the most important task of school education, meets many difficulties and barriers. Many of the causes and determinants of this phenomenon are complex. We can include axiological varieties in social environment and axiological chaos which leads to axiological blindness to the most important determinants. One of the key issues of upbringing towards values is introception of values. In this article, the essence of moral values and outline of theoretical basis of introception of values will be presented in summary form. The author will analyse Core Curriculum of early school education paying special attention to possibilities of introception of moral values. It seems to be necessary to delineate the task for early school education teacher.